Analisis Perbandingan Antara Metode Economic Order Quantity dan Just In Time Untuk Pengendalian Persediaan Pada PT CTI - Ahmad, Fauzan; Al-Faritsy, Ari Zaqi (Sekolah Tinggi Teknologi Dumai, 2024)
PT CTI is a company that produces acrylic derivative souvenirs. A problem occurred in January 2024, there was a shortage of raw materials for 3 color lamps and 3 mm acrylic. This research aims to find out the comparison of the appropriate methods applied in this company, namely between 2 inventory control methods, the EOQ method and the JIT method. The results obtained from this research show that by using the EOQ method for 3 color lamps within a period of 2 months, a quantity of 117 units was obtained, the order frequency was 5 times, and the total inventory cost was IDR 967,774.9. And for 3mm acrylic, within a period of 2 months, the quantity is 1 sheet, the order frequency is 4 times, and the total inventory cost is IDR 788,833. Meanwhile, using the JIT method for 3-color lamps in a period of 2 months, the number was 351 units, the order frequency was 2 times, and the total inventory cost was IDR 887,503.3. And for 3mm acrylic, within a period of 2 months, 2 months, the quantity is 1 sheet, the order frequency is 4 times, the total inventory cost is IDR 239,208.25.